Global Supply Chain Capabilities in Malaysian Textile and Apparel Industry - Khai Loon Lee; Zulkifli Mohamed Udin; Mohamad Ghozali Hassan (International Journal of Supply Chain Management, 2014)
In todays dynamic business environment, the competition is no more between firms; however, between supply chains to gain competitive advantages. This leads to global supply chain. In the global supply chains, the potential of global supply chain capabilities for growth is very promising. Despite the incredible expansion of the industry, particularly Malaysian textile and apparel supply chain, there has been relatively a handful academic study that looked specifically in the area of global supply chain capabilities and performance. This resulting in very little attention has been paid to the power of global supply chain capabilities by researchers and practitioners. This study is derived from the concept of resource based view in supply chain management. This study aims to investigate the relationship between global supply chain capabilities and supply chain performance in Malaysian textile and apparel industry. By thorough reviewing the supply chain management literatures, this study found that there is a relationship between global supply chain capabilities, namely relational capability, technological capability, and organizational culture capability, and supply chain performance. From the underpinning theory and thorough literature review of the study area, this study provides a unique theoretical framework intended to aid researchers and practitioners to develop a more comprehensive understanding of the linkages between global supply chain capabilities and supply chain performance.